Transmissão DSL em modo fantasma: medições e avaliação de desempenho - GOMES, Diego de Azevedo (Universidade Federal do Pará, 2013)
Demand for bit rate is increasing every year, mainly due to the incorporation of online applications into people's life. So the companies which provide this type of service are always investing in research for technologies that enable increased bit rate with a good value for money. Following this perspective, this paper presents transmission phantom mode, which aims to increase the overall rate of transmission of bits in DSL systems when multiple copper pairs available. Here we also show results and discussions on performance of phantom mode. We discuss procedures for performing measurements in phantom mode at frequencies from 100 kHz to 300 MHz, in a way that allows the measurement of phantom mode and deferential mode with the same setup. New results are presented on the direct channel, far-end crosstalk (FEXT) and mode conversion for a Cat-5e cable of 50 meters. Among other facts, we verify large deference’s in the direct channel phantom mode when comparing rolled and unrolled cable measurements, and that manner how we build the phantom mode greatly inuences the behavior of the curves of direct channel, FEXT and mode conversion. We also present results of estimating bit rate when using phantom mode and deferential mode simultaneously, and observed that there is a gain of up to 60 when we use this two modes and vectoring.